Management of the pharmacological treatment in patients with chronic obstructive pulmonary disease - Bastos, Celeste; Vieira, Sílvia; Lima, Ligia (My University, 2019)
Background: Chronic obstructive pulmonary disease (COPD) is a chronic and incapacitating disease, whose regimen includes inhalation medication. The evidence shows a low adherence, which may increase the aggravation of the disease. Objectives: To study the adherence and the perceived competence of patients to comply with the treatment regimen of COPD and evaluate their knowledge on the use of inhalers. Methodology: Quantitative and cross-sectional study, participants were 45 patients with COPD. We used the Medication Adherence Rating Scale (MARS), the Perceived Competence Scale (PCS), and a questionnaire on the use of inhalers. Results: Participants reported good adherence to the medication regimen and reported a high degree of perceived competence to maintain the treatment regimen of COPD. However, they manifested little knowledge about the use of inhalers and the inhalation technique, which compromises the effectiveness of the established therapeutic plans and exacerbate the deterioration of the clinical condition. Conclusion: This study suggests that nursing care should be developed with a focus on knowledge and training in the inhalation technique.

Enquadramento: A doença pulmonar obstrutiva crónica (DPOC) é uma doença crónica e incapacitante, cujo regime terapêutico inclui medicação por via inalatória. A evidência revela uma baixa adesão terapêutica, o que pode potenciar o agravamento da doença. Objetivos: Estudar a adesão e a competência percebida das pessoas para cumprirem o regime de tratamento da DPOC e avaliar o seu conhecimento sobre o uso de inaladores. Metodologia: Estudo quantitativo e transversal. Participaram 45 pessoas com DPOC. Utilizou-se a Escala de Adesão aos Medicamentos, a Escala de Competência Percebida e um questionário sobre o uso de inaladores. Resultados: Os participantes relataram uma boa adesão ao regime medicamentoso e reportaram um elevado grau de perceção de competência para manter o regime de tratamento da DPOC. No entanto, revelaram poucos conhecimentos sobre o uso dos inaladores e a técnica inalatória, o que compromete a eficácia dos planos terapêuticos instituídos e potenciam o agravamento da condição clínica. Conclusão: Este estudo sugere que sejam desenvolvidos cuidados de enfermagem centrados nos conhecimentos e no treino da técnica inalatória.
Gestão do regime farmacológico em doentes com doença pulmonar obstrutiva crónica
Keywords: Pulmonary disease; Chronic obstructive; Medication adherence; Perceived competence; Inhalers